A general synthesis approach for amorphous noble metal nanosheets - Geng Wu; Xusheng Zheng; Peixin Cui; Hongyu Jiang; Xiaoqian Wang; Yunteng Qu; Wenxing Chen; Yue Lin; Hai Li; Xiao Han; Yanmin Hu; Peigen Liu; et al. (Nature Communications, 2019)
While noble metal usage in catalysis is ubiquitous, the metals’ scarcity necessitates new materials designs for efficient utilization. Here, authors report a general strategy to prepare amorphous noble metal nanosheets and find the nanomaterials to act as efficient water-splitting electrocatalysts.